Spectrophotometric determination of ranitidine hydrochloride (RNH) in pharmaceutical formulation using 9-fluorenylmethyl chloroformate (FMOC-Cl) - Elbashir, Abdalla Ahmed; Merghani, Shahd Moutasim (Asian Journal of Pharmaceutical Research and Development, 2018)
A new, simple and sensitive spectrophotometric method is developed for the determination of ranitidine hydrochloride (RNH). The proposed method is based upon reaction of RNH with 9-fluorenylmethyl chloroformate (FMOC-Cl) in borate buffer of pH 8.0 producing an absorption maximum at 255 nm. All parameters required for the reaction conditions are investigated. Linearity is verified with a range of 2-16 μg/mL and is described by the regression equation y = 61129 x + 0.0354 with a correlation coefficient of 0.9998 (n = 7). The limit of detection (LOD) and the limit of quantification (LOQ) were calculated as per ICH guidelines and were found to be 0.2219 and 0.6724 μg/mL, respectively. The method was successfully applied for the determination of RNH in pharmaceutical formulation. Therefore, the method can be used for routine analysis of RNH in quality control laboratories.